Literasi di Perpsutakaan Bina Pustaka Desa Sungai Rambah Berbasis Inklusi Sosial - Azwar Azwar (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2026)
The diversity of social backgrounds presents a unique challenge for village libraries. The Bina Pusaka Library in Sungai Rambah Village is designed to provide services to the surrounding community. The village community comes from diverse educational, economic, and ethnic backgrounds. This research was conducted to determine the process of social inclusion-based literacy services. This research used qualitative methods. The results revealed that the implementation of social inclusion-based literacy was carried out in a scheduled and planned manner. This literacy program was also carried out in collaboration with the village government to ensure its success.